E-Learning Solusi Pembelajaran Online Pandemi Covid-19 Mahasiswa di Kota Medan - Sholeha, Dewi (Impression : Jurnal Teknologi dan Informasi, 2022)
This study aims to determine electronic learning (e-learning) to improve students' analytical skills during the Covid-19 Pandemic. The research population is the first semester students of the University in Medan City with the sample taken at random. Data collection techniques used observation, documentation studies, and analytical thinking skills tests, and were analyzed using paired sample t-test. This research shows the ineffectiveness of using e-learning as a substitute for conventional lectures (non-e-learning). But even so, the average analytical thinking ability of the e-leaning group is also quite large, namely 71.21 so e-learning is also quite good to use, but maybe not as a substitute for conventional learning, but as a supplement (additional) and/or complement. (complementary) learning.